2015
DOI: 10.1016/j.biomaterials.2015.02.100
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the degradation rates of thermally responsive hydrogels designed for soft tissue injection by varying the autocatalytic potential

Abstract: The ability to modulate the degradation properties of biomaterials such as thermally responsive hydrogels is desirable when exploring new therapeutic strategies that rely on the temporary presence of a placed scaffold or gel. Here we report a method of manipulating the absorption rate of a poly(N-isopropylacrylamide) ((poly(NIPAAm)) based hydrogel across a wide range (from 1 d to 5 mo) by small alterations in the composition. Relying upon the autocatalytic effect, the degradation of poly(NIPAAm-co-HEMA-co-MAPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 56 publications
(50 reference statements)
0
32
0
Order By: Relevance
“…At 3 d, 1 w and 2 w after MI, hydrogel that was fluorescently labeled by the incorporation of a green fluorescent monomer during polymer synthesis was injected into the infarction zone and rats were sacrificed within 30 min after the injections [24]. As shown in the tissue sections of Figure 5, the injected hydrogel formed distinct volumes in the LV wall.…”
Section: Resultsmentioning
confidence: 99%
“…At 3 d, 1 w and 2 w after MI, hydrogel that was fluorescently labeled by the incorporation of a green fluorescent monomer during polymer synthesis was injected into the infarction zone and rats were sacrificed within 30 min after the injections [24]. As shown in the tissue sections of Figure 5, the injected hydrogel formed distinct volumes in the LV wall.…”
Section: Resultsmentioning
confidence: 99%
“…This increase is likely the contribution of VP as PVP is highly hydrophilic. Previous studies have demonstrated that copolymerization of NIPAAm with hydrophilic components like HEMA, acrylic acid, propylacrylic acid, and methacrylic acid can increase thermal transition temperatures of PNIPAAm [48, 50, 51, 68]. …”
Section: Discussionmentioning
confidence: 99%
“…The MAPLA was synthesized as previously described [12]. Poly(NIPAAm-co-VP-co-MAPLA) copolymers were synthesized from NIPAAm, VP, and MAPLA by free radical polymerization.…”
Section: Methodsmentioning
confidence: 99%
“…Injection studies in rats were performed as previously described except that the end point was set at 28 days after injection [12]. …”
Section: Methodsmentioning
confidence: 99%